ALMA's view of the M-dwarf GSC 07396-00759's edge-on debris disc: AU Mic's coeval twin. Issue 4 (28th February 2022) - Cronin-Coltsmann, Patrick F; Kennedy, Grant M; Adam, Christian; Kral, Quentin; Lestrade, Jean-François; Marino, Sebastian; Matrà, Luca; Murphy, Simon J; Olofsson, Johan; Wyatt, Mark C
ABSTRACT: We present new ALMA Band 7 observations of the edge-on debris disc around the M1V star GSC 07396-00759. At ∼20 Myr old and in the β Pictoris Moving Group along with AU Mic, GSC 07396-00759 joins it in the handful of low-mass M-dwarf discs to be resolved in the sub-mm. With previous VLT/SPHERE scattered light observations, we present a multiwavelength view of the dust distribution within the system under the effects of stellar wind forces. We find the mm dust grains to be well described by a Gaussian torus at 70 au with a full width at half-maximum of 48 au and we do not detect the presence of CO in the system. Our ALMA model radius is significantly smaller than the radius derived from polarimetric scattered light observations, implying complex behaviour in the scattering phase function. The brightness asymmetry in the disc observed in scattered light is not recovered in the ALMA observations, implying that the physical mechanism only affects smaller grain sizes. High-resolution follow-up observations of the system would allow investigation into its unique dust features as well as provide a true coeval comparison for its smaller sibling AU Mic, singularly well-observed amongst M-dwarfs systems.